Atención de enfermería durante el puerperio, en el Hospital Téofilo Dávila de Machala, 2017. - Burneo Cárdenas, Gabriela Tatiana (2017)
Maternal and child health is a priority established in the Community, Intercultural Model of Comprehensive Family Health Care, therefore, the role of the nursing professional is essential in order to contribute to decrease maternal morbidity and mortality. The current descriptive, cross-sectional research was performed in the Gynecological-Obstetrics service of the “Teófilo Dávila” Hospital in the city of Machala Located in the Zone 7, pursuing as a general objective to determine the application of care standards during the immediate and mediate postpartum period by the professional nursing staff and users' opinions, it was performed with a sample of 175 admitted patients and 17 nurses working in the services of Obstetrics and Gynecology, to obtain information, a questionnaire was applied based on the regulations established by the Ministry of Public Health. The results show that 90% of nurses apply the care standards in the immediate-mediate postpartum period and according to the patients' opinion they recognize the care provided by the nursing professional in the immediate postpartum period, being the most assertive activity the control of the vital signs, in terms of the mediate puerperium period puerperal mothers think that care decreases in percentage, the activities less recognized by the users are the daily bath or perineal hygiene and education in family planning. Therefore, it is concluded that the nursing professional complies in a high percentage with the normative and the users that are the object of the care differ in opinion about the offered care. Keywords: Puerperium, normative, nursing care, perception of the puerpera.